Tailoring Coherent Microwave Emission from a Solid‐State Hybrid System for Room‐Temperature Microwave Quantum Electronics - Kaipu Wang; Hao Wu; Bo Zhang; Xuri Yao; Jiakai Zhang; Mark Oxborrow; Qing Zhao (Advanced Science)
Abstract Quantum electronics operating in the microwave domain are burgeoning and becoming essential building blocks of quantum computers, sensors, and communication devices. However, the field of microwave quantum electronics has long been dominated by the need for cryogenic conditions to maintain delicate quantum characteristics. Here, a solid‐state hybrid system, constituted by a photo‐excited pentacene triplet spin ensemble coupled to a dielectric resonator, is reported for the first time capable of both coherent microwave quantum amplification and oscillation at X band via the masing process at room temperature. By incorporating external driving and active dissipation control into the hybrid system, efficient tuning of the maser emission characteristics at ≈9.4 GHz is achieved, which is key to optimizing the performance of the maser device. The work not only pushes the boundaries of the operating frequency and functionality of the existing pentacene masers but also demonstrates a universal route for controlling the masing process at room temperature, highlighting opportunities for optimizing emerging solid‐state masers for quantum information processing and communication.